Local Spatial Polarization Induced Efficient Charge Separation of Squaraine‐Linked COF for Enhanced Photocatalytic Performance. (15th December 2021) - Ben, Haijie; Yan, Gaojie; Liu, Haiyang; Ling, Cancan; Fan, You; Zhang, Xiaojie
Abstract: The efficiencies of semiconductor photocatalysis are always severely restricted by the rapid recombination of charge carriers in the bulk phase, while local polarization is an efficient scenario to conquer the above issue to boost the photocatalytic performance. Here, as a proof‐of‐concept demonstration, local charge polarization induced by the intrinsic zwitterionic resonance structure of photocatalysts is reported. A novel squaraine‐based covalent organic framework (SQ‐COF‐1) photocatalyst with an interesting zwitterionic resonance structure is creatively developed. Meanwhile, the comparison samples (SQ‐COF‐2 and PDA‐COF) based on similar COF structure with tunable local polarity are accordingly designed and prepared. The local charge polarization generated from the zwitterionic resonance structure profoundly redistributes and separates the charge carriers, as evidenced by experimental and theoretical results collectively. Benefiting by the largest local polarization, SQ‐COF‐1 exhibits superior visible‐light‐driven photocatalytic activities than SQ‐COF‐2, PDA‐COF, and commonly used polymeric carbon nitride photocatalyst. This work presents a local charge polarization protocol for engineering charge behavior to promote photocatalysis, which shows great promise for the future design of high‐performance photocatalytic materials. Abstract : Local charge polarization is induced by a creatively designed zwitterionic resonance structure of a novel squaraine‐based covalent organic framework 1 photocatalyst, effectively promoting its bulk photogenerated charge carriers separation, and largely enhancing its photocatalytic performance.